KIT D816 mutated/CBF-negative acute myeloid leukemia: a poor-risk subtype associated with systemic mastocytosis - Jawhar, Mohamad; Kreil, Sebastian; Schwaab, Juliana; Naumann, Nicole; Metzgeroth, Georgia; Fabarius, Alice; Klein, Stefan; Hofmann, Wolf-Karsten; Reiter, Andreas (Leukemia, 2019)
KIT D816 mutations (KIT D816mut) are strongly associated with systemic mastocytosis (SM) but are also detectable in acute myeloid leukemia (AML), where they represent an adverse prognostic factor in combination with core binding factor (CBF) fusion genes. Here, we evaluated the clinical and molecular features of KIT D816mut/CBF-negative (CBFneg) AML, a previously uncharacterized combination. All KIT D816mut/CBFneg cases (n = 40) had histologically proven SM with associated AML (SM-AML). Molecular analyses revealed at least one additional somatic mutation (median, n = 3) beside KIT D816 (e.g., SRSF2, 38%; ASXL1, 31%; RUNX1, 34%) in 32/32 (100%) patients. Secondary AML evolved in 29/40 (73%) patients from SM ± associated myeloid neoplasm. Longitudinal molecular and cytogenetic analyses revealed the acquisition of new mutations and/or karyotype evolution in 15/16 (94%) patients at the time of SM-AML. Median overall survival (OS) was 5.4 months. A screen of two independent AML databases (AMLdatabases) revealed remarkable similarities between KIT D816mut/CBFneg SM-AML and KIT D816mut/CBFneg AMLdatabases (n = 69) with regard to KIT D816mut variant allele frequency, mutation profile, aberrant karyotype, and OS suggesting underlying SM in a significant proportion of AMLdatabases patients. Bone marrow histology and reclassification as SM-AML has important clinical implications regarding prognosis and potential inclusion of KIT inhibitors in treatment concepts.